SBS elastomer modified asphalt waterproofing coiled material and production process thereof

CN122645706APending Publication Date: 2026-08-28SHANDONG JINLAN BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611041599.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种SBS弹性体改性沥青防水卷材,以解决传统防水卷材在复杂工况下易发生层间剥离与老化开裂的技术问题

Benefits of technology

硅烷偶联剂接枝于滑石粉表面,苯乙烯-丁二烯-苯乙烯嵌段共聚物和氢化苯乙烯-丁二烯-苯乙烯嵌段共聚物在沥青基体中呈现连续的三维半互穿聚合物网络,无相分离聚集现象,证明了微交联体系的稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of building waterproof materials, in particular to SBS elastomer modified asphalt waterproof coiled material and a production process thereof; the SBS elastomer modified asphalt waterproof coiled material comprises a bottom isolation layer, a lower coating cover layer, a polyester base reinforcing layer, an upper coating cover layer and a top isolation layer, and is formed through a composite molding step; the system combines multilayer co-extrusion and interface anchoring to construct an overall layered interlocking structure; the core is to utilize SBS and hydrogenated styrene-butadiene-styrene block copolymer dynamic micro-crosslinking to form a three-dimensional semi-interpenetrating polymer network, introduce microwave pre-activation waste rubber powder to produce mechanical interlocking, and supplement coupling modified talc powder to strengthen the interface anchoring of the coating material and the pre-impregnated base layer; through multiple phase interface synergy and network micro-crosslinking, the application improves the puncture resistance and weather resistance and crack resistance of the coiled material, and overcomes the technical defects of interlayer peeling and aging cracking under complex working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building waterproofing materials technology, specifically to an SBS elastomer modified bitumen waterproof membrane and its production process. Background Technology

[0002] As the requirements for waterproofing quality in construction projects continue to increase, traditional SBS modified bitumen waterproof membranes have shown certain limitations under complex working conditions. At present, a simple multi-layer composite process is generally used, but the layers rely solely on physical adhesion. When subjected to long-term temperature changes, ultraviolet radiation, and substrate strain, stress concentration easily occurs at the interface, leading to interlayer delamination. Furthermore, SBS in traditional modified bitumen systems is prone to degradation under thermo-oxidative aging and ultraviolet radiation, leading to a decrease in weather resistance and aging cracking of waterproof membranes after long-term service. Therefore, how to enhance the interfacial anchoring bond between the multi-layer structure of waterproof membranes and effectively improve the weather resistance and crack resistance of the materials has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0003] The purpose of this invention is to provide an SBS elastomer-modified bitumen waterproof membrane to solve the technical problems of interlayer delamination and aging cracking that occur in traditional waterproof membranes under complex working conditions. The specific technical solution is as follows: An SBS elastomeric modified bitumen waterproof membrane comprises, from bottom to top, a bottom isolation layer, a bottom coating layer, a polyester base reinforcement layer, a top coating layer, and a top isolation layer; The upper coating layer and the lower coating layer are respectively bonded to the upper and lower surfaces of the polyester base reinforcement layer; The upper and lower coating layers have a three-dimensional semi-interpenetrating polymer network structure, which is formed by dynamic micro-crosslinking of styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer under the action of a composite crosslinking agent containing sulfur and tetramethylthiuram disulfide. The upper and lower coating layers also contain waste rubber powder that has been pre-activated by microwave desulfurization, and the waste rubber powder has a micro-crosslinked structure with the three-dimensional semi-interpenetrating polymer network structure. The polyester base reinforcement layer is a porous polyester base pre-impregnated with base asphalt. The upper and lower coating layers contain coupling modified talc powder, which is bonded to the polyester base reinforcement layer through the coupling modified talc powder.

[0004] Preferably, the upper coating layer and the lower coating layer are composed of a composite modified asphalt material. By weight, the raw materials for preparing the composite modified asphalt material include: 100 parts of mixed asphalt matrix, 4-12 parts of styrene-butadiene-styrene block copolymer, 3-8 parts of hydrogenated styrene-butadiene-styrene block copolymer, 5-15 parts of pre-activated waste rubber powder, 10-20 parts of coupling modified talc powder, 5-10 parts of naphthenic oil, and 0.1-0.5 parts of composite crosslinking agent.

[0005] Preferably, the thickness of the upper coating layer is 1.0-1.5 mm, and the thickness of the lower coating layer is 1.0-1.5 mm.

[0006] Preferably, the raw materials for preparing the pre-activated waste rubber powder include 60-80 mesh waste rubber powder and tall oil at a mass of 2% of the waste rubber powder; the pre-activated waste rubber powder is obtained by uniformly mixing the waste rubber powder and tall oil and then irradiating it with microwave power of 800W for 3-5 minutes.

[0007] Preferably, the coupling-modified talc powder is prepared by the following steps: mixing silane coupling agent, ethanol and water evenly, adding glacial acetic acid to adjust the pH to 3.5-4.5, stirring and hydrolyzing for 30 minutes to obtain a hydrolysate; atomizing the hydrolysate and spraying it onto the surface of talc powder in a high-speed mixer, and dispersing and dehydrating it at 110-120°C.

[0008] Preferably, in the hydrolysate, the mass fraction of the silane coupling agent is 5%, and the volume ratio of the ethanol to the water is 9:1; the mass of the silane coupling agent in the hydrolysate is 1.5% of the mass of the talc powder, and the silane coupling agent is 3-methacryloyloxypropyltrimethoxysilane.

[0009] Preferably, the mixed asphalt matrix is ​​composed of 10# asphalt and 100# asphalt in a mass ratio of 1:1 to 1:3; the composite crosslinking agent is composed of sulfur and tetramethylthiuram disulfide, and the mass ratio of sulfur to tetramethylthiuram disulfide is 3:1.

[0010] Preferably, the process includes the following layered composite steps: S1. Preparation of composite coating: The mixed asphalt matrix is ​​heated to 160℃ and melted, naphthenic oil is added and stirred evenly, then styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer are added, the temperature is raised to 185-190℃ and high-shear emulsification is carried out at 4000-5000 rpm for 1.5-2 hours; then the speed is reduced to 800-1000 rpm, and composite crosslinking agent, preactivated waste rubber powder and coupling modified talc powder are added in sequence, stirring is continued and the mixture is kept at 185℃ for 1-1.5 hours, and then allowed to stand to degas, to obtain the composite modified asphalt material; S2. Multi-layer co-extrusion composite molding: After the polyester base reinforcement layer is pre-impregnated with base asphalt at 150°C, the composite modified asphalt material obtained in step S1 is uniformly co-extruded and coated onto the upper and lower surfaces of the polyester base reinforcement layer through a multi-roller double-sided coating machine to form the upper coating layer and the lower coating layer, respectively; then the top isolation layer and the bottom isolation layer are respectively covered on the outside of the upper coating layer and the lower coating layer, and calendered by cooling water roller to form a multi-layer composite SBS elastomer modified asphalt waterproof membrane.

[0011] The beneficial effects of this invention are as follows: When silane coupling agents are grafted onto the surface of talc, styrene-butadiene-styrene block copolymers and hydrogenated styrene-butadiene-styrene block copolymers exhibit a continuous three-dimensional semi-interpenetrating polymer network in the asphalt matrix, without phase separation and aggregation, demonstrating the stability of the micro-crosslinked system. Based on the multi-layer structure design and the synergistic phase regulation of styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer and waste rubber powder in the coating layer, the layered interlocking structure improves the puncture resistance of the roll material by more than 35%. The introduction of hydrogenated styrene-butadiene-styrene block copolymer and the combination of dense coupling modified talc powder with cross-linked network interface enable the membrane to retain tensile strength greater than or equal to 88% after undergoing accelerated aging under artificial climate conditions, and the low-temperature flexibility decay does not exceed 2℃. This effectively solves the technical problems of interlayer peeling and aging cracking of traditional waterproof membranes under complex working conditions. Detailed Implementation

[0012] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1: This embodiment yields a high weather-resistant and crack-resistant multilayer composite waterproof membrane with a total thickness of 4.0 mm. The polyester base reinforcement layer is made of 180 g / m² long-filament polyester nonwoven fabric, and the upper coating layer has a thickness of 1.3 mm and the lower coating layer has a thickness of 1.3 mm. The composite modified asphalt materials used, by weight, include: 30 parts of 10# asphalt, 70 parts of 100# asphalt, 8 parts of styrene-butadiene-styrene block copolymer, 5 parts of hydrogenated styrene-butadiene-styrene block copolymer, 10 parts of pre-activated waste rubber powder, 15 parts of coupling modified talc powder, 8 parts of naphthenic oil, 0.15 parts of sulfur, and 0.05 parts of tetramethylthiuram disulfide; S1. Preparation of coupling-modified talc: Prepare a 5% (w / w) ethanol / water solution of 3-methacryloyloxypropyltrimethoxysilane, with a volume ratio of ethanol to water of 9:1. Adjust the pH to 4.0 with glacial acetic acid and stir for 30 min to allow the coupling agent to be fully hydrolyzed. The obtained hydrolysate was atomized and sprayed onto the surface of talc powder, wherein the pure mass of 3-methacryloxypropyltrimethoxysilane was 1.5% of the mass of talc powder; after spraying, it was dispersed and mixed in a high-speed mixer and dehydrated and cured at 120°C to obtain coupling modified talc powder. The function of this coupling modified talc powder is to improve the dispersion state of talc powder in the coating layer and enhance its anchoring bond with the asphalt phase and the impregnation interface of the porous polyester base reinforcement layer. S2. Preparation of pre-activated waste rubber powder: Take 60-mesh waste rubber powder and mix it evenly with tall oil at 2% of the mass of waste rubber powder. Irradiate it under 800W microwave conditions for 4 minutes to obtain pre-activated waste rubber powder. The pre-activated waste rubber powder selectively breaks cross-linking bonds through microwave desulfurization, exposing active groups on its surface to form a mechanical interlocking structure in the layer and undergo micro-crosslinking with the three-dimensional semi-interpenetrating polymer network. S3. Preparation of composite coating: Add 10# asphalt and 100# asphalt into the reactor, heat to 160℃ and melt and mix, add naphthenic oil and stir evenly; add styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer, heat to 185℃, and emulsify and mix under high shear at 4500rpm for 90min. After the polymer has fully swelled, the rotation speed is reduced to 800 rpm, sulfur and tetramethylthiuram disulfide are added, followed by pre-activated waste rubber powder and coupling modified talc powder. The mixture is kept at 185°C for 60 minutes and allowed to stand to degas, thus obtaining a composite modified asphalt material. Its function is to serve as the base material for the upper and lower coating layers, providing a three-dimensional semi-interpenetrating polymer network structure. S4. Multi-layer composite molding: The polyester base reinforcement layer is pre-impregnated with base asphalt at 150℃. The composite modified asphalt material obtained in S3 is coated on the upper and lower surfaces of the base reinforcement layer using a double-sided coating method to form an upper coating layer and a lower coating layer. The total thickness of the roll is controlled to be 4.0mm. After covering both sides with polyethylene release film, it is cooled, calendered and rolled up to obtain a waterproof roll.

[0013] Example 2: In this embodiment, a multi-layer composite waterproof membrane is prepared with a total thickness of 3.5 mm. The polyester base reinforcement layer is made of 180 g / m² long filament polyester non-woven fabric, the upper coating layer has a thickness of 1.0 mm, and the lower coating layer has a thickness of 1.0 mm. The composite modified asphalt material used includes, by weight, 25 parts of 10# asphalt, 75 parts of 100# asphalt, 4 parts of styrene-butadiene-styrene block copolymer, 3 parts of hydrogenated styrene-butadiene-styrene block copolymer, 5 parts of preactivated waste rubber powder, 10 parts of coupling modified talc powder, 5 parts of naphthenic oil, 0.075 parts of sulfur, and 0.025 parts of tetramethylthiuram disulfide. S1. Preparation of coupling modified talc: Coupling modified talc was prepared using the same method as in Example 1. The pure mass of 3-methacryloyloxypropyltrimethoxysilane was controlled to be 1.5% of the mass of talc, and the dehydration and curing temperature was 110°C to obtain coupling modified talc, so as to improve its interfacial compatibility with the organic phase and form a strong anchor bond at the impregnation interface. S2. Preparation of pre-activated waste rubber powder: Take 80-mesh waste rubber powder and mix it evenly with tall oil at 2% of the mass of the waste rubber powder. Irradiate it under 800W microwave conditions for 3 minutes to obtain pre-activated waste rubber powder, so as to selectively break the cross-linking bonds of the waste rubber powder and improve its surface activity. S3. Preparation of composite coating material: The mixed asphalt matrix is ​​heated to 160℃ to melt, and naphthenic oil is added and mixed evenly; styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer are added, and the temperature is raised to 185℃. High shear mixing is carried out at 4000 rpm for 1.5 h; the speed is reduced to 1000 rpm, and sulfur, tetramethylthiuram disulfide, pre-activated waste rubber powder and coupling modified talc are added in sequence. The mixture is kept at 185℃ for 1 h and allowed to stand to degas, thus obtaining the composite modified asphalt material, which serves as the matrix of the coating layer to form a layered interlocking structure; S4. Multi-layer composite molding: After the polyester base reinforcement layer is pre-impregnated with base asphalt at 150℃, the composite modified asphalt material obtained in S3 is co-extruded and coated using a double-sided coating method. The thickness of both the upper and lower coating layers is controlled to be 1.0mm. After covering with a release film, the material is cooled, calendered, and rolled up to obtain a waterproof membrane.

[0014] Example 3: In this embodiment, a multi-layer composite waterproof membrane is prepared with a total thickness of 4.5 mm. The polyester base reinforcement layer is made of 180 g / m² long filament polyester non-woven fabric, the upper coating layer has a thickness of 1.5 mm, and the lower coating layer has a thickness of 1.5 mm. The composite modified asphalt materials used, by weight, include: 50 parts of 10# asphalt, 50 parts of 100# asphalt, 12 parts of styrene-butadiene-styrene block copolymer, 8 parts of hydrogenated styrene-butadiene-styrene block copolymer, 15 parts of pre-activated waste rubber powder, 20 parts of coupling modified talc powder, 10 parts of naphthenic oil, 0.375 parts of sulfur, and 0.125 parts of tetramethylthiuram disulfide; S1. Preparation of coupling modified talc: Coupling modified talc was prepared using the same method as in Example 1. The pure mass of 3-methacryloyloxypropyltrimethoxysilane was controlled to be 1.5% of the mass of talc, and the dehydration and curing temperature was 120°C to obtain coupling modified talc. Its function is to enhance the anchoring bond between the coating layer and the impregnation interface of the porous polyester base reinforcement layer. S2. Preparation of pre-activated waste rubber powder: Take 60-mesh waste rubber powder and mix it evenly with tall oil at 2% of the mass of the waste rubber powder. Irradiate it under 800W microwave conditions for 5 minutes to obtain pre-activated waste rubber powder. This selectively breaks the cross-linking bonds of the waste rubber powder and promotes its micro-cross-linking with the three-dimensional semi-interpenetrating polymer network. S3. Preparation of composite coating material: The mixed asphalt matrix is ​​heated to 160℃ to melt, and naphthenic oil is added and stirred evenly; styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer are added, and the temperature is raised to 190℃. High shear mixing is carried out at 5000 rpm for 2 hours; the speed is reduced to 1000 rpm, sulfur and tetramethylthiuram disulfide are added, and then pre-activated waste rubber powder and coupling modified talc powder are added in sequence. The mixture is kept at 185℃ for 1.5 hours and allowed to stand to degas, thus obtaining a composite modified asphalt material. This material is used to provide upper and lower coating layers with a three-dimensional semi-interpenetrating polymer network structure. S4. Multi-layer composite molding: After the polyester base reinforcement layer is pre-impregnated with base asphalt at 150℃, the composite modified asphalt material obtained in S3 is co-extruded and coated using a double-sided coating method. The thickness of both the upper and lower coating layers is controlled to be 1.5mm. After covering with a release film, the membrane is cooled, calendered, and rolled up to obtain the waterproof membrane.

[0015] Example 4: In this embodiment, a multi-layer composite waterproof membrane is prepared with a total thickness of 4.0 mm. The polyester base reinforcement layer is made of 180 g / m² long filament polyester non-woven fabric, the upper coating layer has a thickness of 1.2 mm, and the lower coating layer has a thickness of 1.2 mm. The composite modified asphalt materials used, by weight, include: 40 parts of 10# asphalt, 60 parts of 100# asphalt, 10 parts of styrene-butadiene-styrene block copolymer, 6 parts of hydrogenated styrene-butadiene-styrene block copolymer, 12 parts of pre-activated waste rubber powder, 18 parts of coupling modified talc powder, 7 parts of naphthenic oil, 0.225 parts of sulfur, and 0.075 parts of tetramethylthiuram disulfide; S1. Preparation of coupling modified talc: Coupling modified talc was prepared using the same method as in Example 1, with the pure mass of 3-methacryloyloxypropyltrimethoxysilane controlled to be 1.5% of the mass of talc, and the dehydration and curing temperature controlled to be 115℃. S2. Preparation of pre-activated waste rubber powder: Take 70-mesh waste rubber powder and mix it evenly with tall oil at 2% of the mass of the waste rubber powder. Irradiate it under 800W microwave conditions for 4 minutes to obtain pre-activated waste rubber powder. S3. Preparation of composite coating: The mixed asphalt matrix is ​​heated to 160℃ to melt, and naphthenic oil is added and mixed evenly; styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer are added, and the temperature is raised to 188℃. High-shear mixing is carried out at 4500 rpm for 100 min; the speed is reduced to 900 rpm, and sulfur, tetramethylthiuram disulfide, preactivated waste rubber powder and coupling modified talc are added in sequence. The mixture is kept at 185℃ for 70 min and allowed to stand to degas, thus obtaining the composite modified asphalt coating. S4. Multi-layer composite molding: After the polyester base reinforcement layer is pre-impregnated with base asphalt at 150℃, the composite modified asphalt coating material obtained in S3 is co-extruded and coated on both sides. The thickness of the upper and lower coating layers is controlled at 1.2mm. After covering with a release film, it is cooled, calendered and rolled up to obtain a waterproof membrane.

[0016] Comparative Example 1: The difference between this comparative example and Example 1 is that SEBS is not added to the composite modified asphalt material, and only 8 parts of SBS are used as polymer modifier. The other raw material composition, operation steps and process parameters are exactly the same as those in Example 1.

[0017] Comparative Example 2: The difference between this comparative example and Example 1 is that the sulfur and tetramethylthiuram disulfide crosslinking system is omitted, while the other raw material composition, operating steps and process parameters are exactly the same as in Example 1.

[0018] Comparative Example 3: The difference between this comparative example and Example 1 is that the pre-activated waste rubber powder in Example 1 is replaced with waste rubber powder of the same mesh size that has not been premixed with tall oil and microwave irradiated, and the amount added is still 10 parts. The other raw material composition, operation steps and process parameters are exactly the same as those in Example 1.

[0019] Comparative Example 4: The difference between this comparative example and Example 1 is that the coupling modified talc in Example 1 is replaced with ordinary talc that has not been treated with KH-570, and the amount added is still 15 parts. The other raw material composition, operating steps and process parameters are exactly the same as those in Example 1.

[0020] Comparative Example 5: The difference between this comparative example and Example 1 is that the basic asphalt pre-impregnation step of the polyester base reinforcement layer is omitted, and double-sided coating is directly performed. The other raw material composition, operation steps and process parameters are exactly the same as those in Example 1.

[0021] Comparative Example 6: The difference between this comparative example and Example 1 is that the waste rubber powder component is omitted, while the other raw material composition, operating steps and process parameters are exactly the same as in Example 1.

[0022] Performance testing and data sheets: Heat resistance, low-temperature flexibility, and puncture resistance were tested according to the conventional methods for roll materials in GB18242-2008; artificial climate aging was carried out by ultraviolet and thermo-oxidative composite aging for 720 hours, and the tensile strength retention rate and low-temperature flexibility changes after aging were tested; peel strength was determined by the peel test between the coating layer and the base layer according to relevant standards such as GB / T328.20-2007. The samples and test results are as follows: Table 1. Performance test results of the roll materials in each embodiment and comparative example.

[0023] As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, the heat resistance, tensile strength retention rate after aging, and low-temperature flexibility all decreased after omitting SEBS. When SBS exists alone, the system is still dominated by the physical swelling and entanglement of polybutadiene segments. At high temperatures, the phase is prone to thermodynamic phase separation, and the unsaturated segments in SBS are more susceptible to the effects of ultraviolet radiation and thermo-oxidative stress. After adding SEBS, the ethylene-butene segments and SBS segments form a more stable interpenetrating structure, and the weather resistance is improved by the hydrogenated structure. Therefore, Example 1 has higher heat resistance and tensile strength retention rate after aging. As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, the heat resistance deteriorated significantly after omitting the composite crosslinking agent, and the peel strength and tensile strength retention rate after aging also decreased simultaneously. When sulfur and tetramethylthiuram disulfide work together, the double bonds in the SBS chain segment can undergo moderate micro-crosslinking, transforming the original physical entanglement into a semi-interpenetrating network with high crosslinking density. Without this crosslinking system, the polymer phase is more prone to relaxation and migration at high temperatures, the roll material’s resistance to flow decreases when heated, and the weakening of network constraints reduces the efficiency of interfacial stress transfer, as well as interlayer bonding and aging stability. As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, after replacing the pre-activated waste rubber powder with unactivated waste rubber powder, the puncture resistance, low-temperature flexibility and the retention rate of tensile strength after aging all decreased; microwave desulfurization treatment can selectively weaken the cross-linking bonds in waste rubber powder, expose a large number of active groups on its surface, and improve its interfacial bonding ability in the asphalt system. Unactivated waste rubber powder has low surface energy and lacks chemical reactivity. It lacks effective chemical bonding with the SBS / SEBS network and is more like ordinary filler particles. When subjected to external force, it is difficult to form effective stress absorption units. Therefore, it fails to meet the puncture resistance and crack resistance requirements specified in the standard. As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, the peel strength was significantly reduced after using unmodified talc, and the heat resistance and the retention rate of tensile strength after aging were also reduced. Ordinary talc powder has insufficient affinity between its surface and the organic phase, and interfacial voids are easily formed around the particles. These voids are more likely to become stress concentration points during the bending, tensioning, and thermal aging of the roll material. After treatment with KH-570, an organic-friendly interface is formed on the surface of the talc powder, which can improve its dispersion in the coating layer and enhance its bonding with the asphalt phase, polymer phase, and the impregnation interface of the base layer. Therefore, the interlayer bonding in Example 1 is stronger, and the performance is better maintained after aging. As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, after omitting the base asphalt pre-impregnation step of the polyester base reinforcement layer, the peel strength is significantly reduced, while the heat resistance and puncture resistance are basically not significantly fluctuated; the role of pre-impregnation treatment is mainly reflected in the filling of pores in the base layer and the formation of the interface transition layer. After the base asphalt is pre-impregnated, the coating material can penetrate more fully into the porous polyester base, forming a continuous impregnation interface. If this step is omitted, although the material properties of the upper and lower coating layers themselves still exist, the mechanical interlocking between the base layer and the coating layer is weakened, and the layers are more likely to peel off along the interface. As can be seen from the comparison of the test results of Example 1 and Comparative Example 6 in Table 1, the puncture resistance decreased most significantly after omitting the waste rubber powder, and the low-temperature flexibility and low-temperature retention after aging also decreased. In Example 1, the waste rubber powder not only played a filling role, but also formed a deformable elastic dispersed phase in the coating layer. When the roll material is subjected to local impact or base layer tension, this dispersed phase can absorb some of the stress and slow down the crack propagation to the surrounding area; without this component, the energy-consuming units inside the material are reduced, and local loads are more likely to act directly on the asphalt continuous phase and the base layer interface, thus reducing the puncture resistance and crack resistance. The test results from Examples 1 to 4 show that, within the scope of the technical solution of this invention, by adjusting the proportions and process conditions of each group, the resulting rolls can maintain high heat resistance, low-temperature flexibility, puncture resistance and aging resistance. In Example 2, when each modified component is added at a low amount, the roll can still meet the requirements for waterproof rolls, but the stress dissipation capacity and interface reinforcement effect are relatively weakened. In Example 3, when the polymer, waste rubber powder, and talc powder are added in higher amounts, the heat resistance and puncture resistance are higher, but the low-temperature flexibility is slightly reduced. In Example 4, the proportions of each component are more balanced, and the heat resistance, low-temperature flexibility, puncture resistance, and aging retention rate show the optimal comprehensive combination relationship.

[0024] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. An SBS elastomeric modified bitumen waterproof membrane, comprising, from bottom to top, a bottom isolation layer, a lower coating layer, a polyester base reinforcement layer, an upper coating layer, and a top isolation layer; characterized in that, The upper coating layer and the lower coating layer are respectively bonded to the upper and lower surfaces of the polyester base reinforcement layer; The upper and lower coating layers contain a three-dimensional semi-interpenetrating polymer network. The three-dimensional semi-interpenetrating polymer network structure is formed by dynamic micro-crosslinking of styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer under the action of a composite crosslinking agent containing sulfur and tetramethylthiuram disulfide. The upper and lower coating layers also contain waste rubber powder that has been pre-activated by microwave desulfurization, and the waste rubber powder has a micro-crosslinked structure with the three-dimensional semi-interpenetrating polymer network structure. The polyester base reinforcement layer is a porous polyester base pre-impregnated with base asphalt. The upper and lower coating layers contain coupling modified talc powder, which is bonded to the polyester base reinforcement layer through the coupling modified talc powder.

2. The SBS elastomer modified bitumen waterproof membrane according to claim 1, characterized in that, The upper coating layer and the lower coating layer are composed of a composite modified asphalt material. By weight, the raw materials for preparing the composite modified asphalt material include: 100 parts of mixed asphalt matrix, 4-12 parts of styrene-butadiene-styrene block copolymer, 3-8 parts of hydrogenated styrene-butadiene-styrene block copolymer, 5-15 parts of pre-activated waste rubber powder, 10-20 parts of coupling modified talc powder, 5-10 parts of naphthenic oil, and 0.1-0.5 parts of composite crosslinking agent.

3. The SBS elastomer modified bitumen waterproof membrane according to claim 1, characterized in that, The thickness of the upper coating layer is 1.0-1.5 mm, and the thickness of the lower coating layer is 1.0-1.5 mm.

4. The SBS elastomer modified bitumen waterproof membrane according to claim 2, characterized in that, The raw materials for preparing the pre-activated waste rubber powder include 60-80 mesh waste rubber powder and tall oil at 2% of the mass of the waste rubber powder; the pre-activated waste rubber powder is prepared by mixing the waste rubber powder and tall oil evenly and then irradiating them with microwave power of 800W for 3-5 minutes.

5. The SBS elastomer modified bitumen waterproof membrane according to claim 2, characterized in that, The coupling-modified talc powder is prepared by the following steps: silane coupling agent, ethanol and water are mixed evenly, glacial acetic acid is added dropwise to adjust the pH to 3.5-4.5, and the mixture is stirred and hydrolyzed for 30 minutes to obtain a hydrolysate; the hydrolysate is atomized and sprayed onto the surface of talc powder in a high-speed mixer, and dispersed and dehydrated and solidified at 110-120℃.

6. The SBS elastomer modified bitumen waterproof membrane according to claim 5, characterized in that, In the hydrolysate, the mass fraction of the silane coupling agent is 5%, and the volume ratio of the ethanol to the water is 9:1; the mass of the silane coupling agent in the hydrolysate is 1.5% of the mass of the talc powder, and the silane coupling agent is 3-methacryloyloxypropyltrimethoxysilane.

7. The SBS elastomer modified bitumen waterproof membrane according to claim 2, characterized in that, The mixed asphalt matrix is ​​composed of 10# asphalt and 100# asphalt in a mass ratio of 1:1 to 1:3; the composite crosslinking agent is composed of sulfur and tetramethylthiuram disulfide, and the mass ratio of sulfur to tetramethylthiuram disulfide is 3:

1.

8. A production process for SBS elastomer modified bitumen waterproof membrane as described in any one of claims 1-7, characterized in that, The following layered composite steps are included: S1. Preparation of composite coating: The mixed asphalt matrix is ​​heated to 160℃ and melted, naphthenic oil is added and stirred evenly, then styrene-butadiene-styrene block copolymer and hydrogenated styrene-butadiene-styrene block copolymer are added, the temperature is raised to 185-190℃ and high-shear emulsification is carried out at 4000-5000 rpm for 1.5-2 hours; then the speed is reduced to 800-1000 rpm, and composite crosslinking agent, preactivated waste rubber powder and coupling modified talc powder are added in sequence, stirring is continued and the mixture is kept at 185℃ for 1-1.5 hours, and then allowed to stand to degas, to obtain the composite modified asphalt material; S2. Multi-layer co-extrusion composite molding: After the polyester base reinforcement layer is pre-impregnated with base asphalt at 150°C, the composite modified asphalt material obtained in step S1 is uniformly co-extruded and coated onto the upper and lower surfaces of the polyester base reinforcement layer through a multi-roller double-sided coating machine to form the upper coating layer and the lower coating layer, respectively; then the top isolation layer and the bottom isolation layer are respectively covered on the outside of the upper coating layer and the lower coating layer, and calendered by cooling water roller to form a multi-layer composite SBS elastomer modified asphalt waterproof membrane.